Pressure of the Grey Heron breeding colony (Ardea cinerea) on the phytocoenosis of lowland acidophilous beech forest in the „Czapliniec w Wierzysku” reserve (Kaszubskie Lake District) - Żółkoś, Katarzyna; Markowski, Ryszard (Biodiversity: Research and Conservation, 2006)
Bird breeding colonies have always a significant influence on the habitats and phytocoenoses they occupy. Longlasting existence of the Grey Heron colony in Wierzysko (over 100 years) has resulted in formation of two different parts of it - a currently occupied area and a post-colony area. Within the colony area, most changes concern the floor flora of Luzulo pilosae-Fagetum phytocoenosis. Plants of different habitats, especially nitrophilous ones, appear. At the same time, some mosses and vascular plants specific for that association decline. In the post-colonized area the spontaneous, but relatively stable, shrub community with elder (Sambucus nigra) domination. The rest part is covered by a low-growing forest community, which has appeared after removing elder and introducing larch (Larix decidua et kaempferi) and partly lime (Tilia cordata). Forest floor in the post-colonized area is distinguishably heterogeneous and consists mostly of forest, clear-cut, meadow and ruderal species, however the floristic composition of the phytocoenoses is unstable. The rate of forest decaying and shifting of the breeding colony in Wierzysko is not very rapid. Spontaneous restoration of forest phytocoenosis is also very slow, probably due to the persistence of enormous soil fertilization and specific biotope as well as the strong influence of Sambucus nigra.